Corrosion Fundamentals and Protection Mechanisms - Zafar, Fahmina; Ghosal, Anujit; Sharmin, Eram (IntechOpen, 2022)
Corrosion in materials is responsible for huge direct as well as indirect losses around the world. To address corrosion, a combinational approach involving molecular simulations of natural inhibitors, pre-structural designs, and the development of traditional but functional polymeric nanocomposites is recommended. This book presents the basics of corrosion from thermodynamic and kinetic points of view, discusses the major driving force behind corrosion, and provides insight into possible remediation techniques.